KEHIDUPAN SOSIAL BUDAYA MASYARAKAT TRANSMIGRAN âSARIAK BAYANGâ DI DESA RITA SARBAINI KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK (1997-2011) - Aprilina, Neneng; Husnita, Liza; Zulfa, Zulfa (Pendidikan Sejarah, 2013)
ABSTRACTÂ One of the areas in West Sumatra Transmigration is Rita Sarbainidikecamatan Valley Village GumantiSolok . The village is a village Transmigration opened in 1997 that the inauguration was attended by the transform ( Minister of Transmigration ) SiswonoYudohusodo when it ( 1988-1993 ) and the Solok regent GamawanFauzi , who served from the years ( 1995-2005 ). Field research is useful for resources that are primary and secondary . The primary source is done by way of interviews, and secondary sources found through library research include Gumanti Valley District and Solok Yearbook Yearbook as well as some relevant books about the transmigration. These results indicate that , before the transmigration program was held in SariakBayang , which is about 1996 people so far away from the progress of time because the forest is wilderness , farming pattern they use is still traditional , Once they lived in Rita Sarbaini , traditional farming practices are not can be applied again , they should be able to utilize the land that was given to the seed received from the government . Conclusions of this thesis can be seen from the development of migrants in how to get along , organizational , collaboration , and interaction with the people who run smoothly . In addition, the social and cultural changes for the transmigration , they left the old culture and the new culture of wear as it is run by a native of Rimbo Data . Even now the relationship between the indigenous migrant communities are good without any more difference . Keywords: Transmigration,Society, cultural, social